Finishing Touch user's preference on exterior color finishes in residential buidings - Villar, Marvin M. (Quezon City College of Architecture, University of the Philippines Diliman, 2011)
The study aims to understand the preference of selected users is Quezon City on exterior color finishes of residential building and categorize the prevalent typology based on the evaluation's identified factors: Color Value(Lightness and darkness), Color Category (warm and Cool) and Color Scheme(Mono-Chromatic,Complimentary,Analogous and Triadic). The identified users of the study were grouped based on the demographic categories such as gender, age, occupation, and socio-economic classification. (i.e. such as high-income level, middle-income level and low-income level). Structured questionnaires and a color selection palette with attached model house images were used in the survey. The research study showed that there are differences in of color preferences among users. Based on their demographic category. For example, users from the high-income level have different color preferences compared to users from the low-income level while female users have different color preferences compared to male users. The results of the analyses were tabulated and analyzed using various statistical models to significantly correlate the various responses of users on the issue of exterior color finishes.
Vita.
Thesis (Master of Architecture) - - University of the Philippines Diliman.